Giving hihi a helping hand: assessment of alternative rearing diets in food supplemented populations of an endangered bird. (31st January 2013) - Walker, L. K.; Armstrong, D. P.; Brekke, P.; Chauvenet, A. L. M.; Kilner, R. M.; Ewen, J. G.
Abstract: Providing supplementary food to endangered bird species is a common management action. Research has tended to focus on whether or not supplementary food should be provided, and relatively less attention has been paid to the form that food should take. Supplementation is also commonly made directly to adult individuals. However, the potentially long‐lasting consequences of developmental diet make it relevant to consider what type of supplementary food is most appropriate for nestling birds. We sought to explore these issues in a wild population of hihi ( Notiomystis cincta ), an endangered New Zealand passerine in which adults in four out of five extant populations receive supplementary food. We directly provisioned nestling hihi with four alternative dietary treatments (protein‐ or carbohydrate‐based diet with or without carotenoids) and assessed the effect of supplementation on1 nestling growth parameters;2 survival from hatching to fledging;3 survival from fledging to recruitment (breeding age). Firstly, we found a sex‐specific effect of protein supplementation on growth inflection point: inflection point was later for females that received a high‐protein diet compared with controls, and earlier for males. Secondly, we found an interacting effect of sex and diet on survival from hatching to fledging, such that females benefitted from a high‐protein diet while males suffered. We also found an interacting effect of protein treatment and carotenoid treatment on survival to fledging, such that the positive effects of carotenoid supplementation were negated if carotenoids were provided in combination with the protein supplement. Finally, we were unable to detect an effect of nestling dietary treatment on survival from fledging to recruitment. Our results suggest that the short‐term consequences of nestling supplementary feeding are more pronounced than any long‐term effects. We also found evidence that dietary supplementation had opposing effects on male and female nestlings, which may be an important, previously overlooked, consideration when evaluating the conservation value of feeding regimes.